Cowboy metaphysics ethics and death in westerns - French, Peter A. 1942- (Rowman & Littlefield, 1997)
"Peter A. French examines the world of the western, one in which death is annihilation, the culmination of life, and there is nothing else. In that world, he finds alternatives to Judeo-Christian traditions that dominate our ethical theories, alternatives that also attack the views of the most prominent ethicists of the past three centuries."
Keywords: Cowboys; Dood; Films; Ethik; Film; Western films -- Moral and ethical aspects; Western -- Film; Tod